Production and preservation quality assessment of canned beef - Roy, BK; Sultana, N; Khanam, JS; Tule, SA (Meat Research, 2024)
The present study was undertaken to produce canned beef along with the determination of its preservation quality. Kalojira oil (Nigella sativa), Na-nitrite (NaNO2 ) and common salt (NaCl) were added in beef and treated as preservative groups namely T1 , T2 and T3 treatment group respectively. Beef without addition of any preservative kept as control group (T0 ) and each group or treatment containing three (03) replications. Data from both fresh raw beef and canned beef were compared statistically in an ANOVA of a Completely Randomized Design using General Linier Model Procedures of SPSS, 20 computer software packages. Beef was purchased from local market immediate after slaughter and brought at meat processing laboratory of BLRI. The physicochemical properties and microbiological properties of both raw beef and canned beef were recorded. The physical properties viz, pH, drip and cook loss of fresh raw beef were 6.40, 5.55% and 27.71%, respectively. The moisture and CP content in raw beef were 74.61 and 25.39%, respectively. The total viable bacteria count and Coliform count in raw beef were 8.8 × 106 and 4.3 × 104 cfu/g, respectively. The pH of canned beef was higher (p < 0.05) in meat preserved with NaNO2 and Kalojira oil than that of NaCl and control group. Preservatives, however, had no effects (p > 0.05) on moisture or DM and CP content in canned beef. Though, there was no significant (p > 0.05) effect, but Kalojira oil performed as impressive preservative compared to others. In microbiological aspects of canned meat, the TVC, TCC, Salmonella spp. and Staphylococcus spp. were entirely absent in Kalojira group. In case of NaNO2 and NaCl group, only a very few numbers of viable bacteria were found (1 × 102 ). On the other hand, only the Staphylococcus bacteria were found in case of control group. Considering the physico-chemical and microbiological aspects in canned beef, it may be concluded that the Kalojira oil could be a suitable value-added preservative in meat canning.